2021
DOI: 10.1021/acs.est.1c01131
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the High-Activity Origin of Single-Atom Iron Catalysts for Organic Pollutant Oxidation via Peroxymonosulfate Activation

Abstract: Single-atom catalysts (SACs) have emerged as efficient materials in the elimination of aqueous organic contaminants; however, the origin of high activity of SACs still remains elusive. Herein, we identify an 8.1-fold catalytic specific activity (reaction rate constant normalized to catalyst’s specific surface area and dosage) enhancement that can be fulfilled with a single-atom iron catalyst (SA-Fe-NC) prepared via a cascade anchoring method compared to the iron nanoparticle-loaded catalyst, resulting in one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 267 publications
(111 citation statements)
references
References 35 publications
3
94
0
Order By: Relevance
“…The specific activity of CoN x catalysts is found to be linearly related to the Bader charges of Co single atom and the most electron‐poor C atom adjacent to pyridinic N in CoN x models (Figure 4b), but the regression coefficient of the former is slightly higher than that of the latter, which suggests that the electron density of single Co atom mainly governs the Fenton‐like performance of CoN x . Our previous works [ 6–8 ] demonstrated that the electron‐rich and electron‐deficient areas were responsible for PMS reduction and oxidation, respectively. In the case of CoN x for PMS activation, the electron‐rich single Co atoms and electron‐poor pyridinic N‐coordinated C atoms can act as catalytic sites toward PMS adhesion and successive conversion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The specific activity of CoN x catalysts is found to be linearly related to the Bader charges of Co single atom and the most electron‐poor C atom adjacent to pyridinic N in CoN x models (Figure 4b), but the regression coefficient of the former is slightly higher than that of the latter, which suggests that the electron density of single Co atom mainly governs the Fenton‐like performance of CoN x . Our previous works [ 6–8 ] demonstrated that the electron‐rich and electron‐deficient areas were responsible for PMS reduction and oxidation, respectively. In the case of CoN x for PMS activation, the electron‐rich single Co atoms and electron‐poor pyridinic N‐coordinated C atoms can act as catalytic sites toward PMS adhesion and successive conversion.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, the pyridinic N‐coordinated electron‐poor C atoms are responsible for PMS oxidation resulting in the production of PMS anion radical (SO 5 •‒ ), which subsequently transforms into singlet oxygen ( 1 O 2 ) through reaction with water molecules, consistent with previous works. [ 6–8,37 ] In this context, the CoN 4 catalyst with single‐atomic Co–pyridinic N 4 moiety possesses more electron‐deficient C atoms adjacent to pyridinic N should produce the larger amount of 1 O 2 resulting from PMS oxidation, which is evidenced by the stronger 1 O 2 signal intensity for the EPR spectrum of CoN 4 /PMS as compared to that for CoN 3 /PMS (see Figure 3b above). However, the further decrease of coordination number to two for CoN x in turn enhances the generation of 1 O 2 in CoN 2 /PMS (Figure 3b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the generation of COH, SO 4 C À , and other radicals have not been eliminated to date. [12] Furthermore, the sparse doping of N, which fixes the metal atoms by coordination, causes the low metal loading, which retards the generation of 1 O 2 . [13] Therefore, the SACs having uniformly structured supports and abundant active sites are required for the selective generation of 1 O 2 .…”
mentioning
confidence: 99%
“…Conceptually, the pyrolysis method means that the metal precursor is dispersed through a space confinement strategy, and then the precursor material is reduced by high‐temperature heating to generate a single‐atom catalyst in situ 108,132 . The pyrolysis method is widely applicable to various carriers, such as zeolite, 133 MOFs, 134 covalent organic frameworks (COFs), 135,136 g‐C 3 N 4 83,137 ‐modified carbon‐based materials, 138,139 and so on.…”
Section: Synthetic and Characterization Methods For Single‐atom Catal...mentioning
confidence: 99%